Inclusive Access and Open Educational Resources E-text Programs in Higher Education - Hurley, Tracy A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This volume takes a comprehensive and broad look at e-text programs across a wide spectrum of programs, institutions, and policies in three parts. The first part showcases several policy papers to contextualize the discussion and highlight the reasons for IAE programs$1 (Bstructure and the obstacles they face for implementation. The second part is an in-depth exploration of various case studies that provide a detailed description of IAE programs, including information about program elements, program structure, program size, and insights into how programs are operationalized, and their shortcomings and benefits to students and stakeholders. The final part is a selection of research papers that offer evidence-based support for the adoption of IAE programs in terms of student success, access, engagement, costs, and a variety of other student and institutional outcomes. There are approximately 300 institutions of higher education that currently have some form of Inclusive Access or Open Educational Resources E-text (IAE) program in the United States, but there is little scholarship that engages on the topic of assessing these programs$1 (Beffect on student success. The results of the research studies included in this volume will inform faculty, administrators, and policy-makers who seek to support the development, adoption, and implementation of IAE programs based on their potential positive effects on student success and other outcomes.s
Part I: Policies -- Chapter 1: Federal Policies, the Veterans Administration, and the U.S. Department of Education Regarding Inclusive Access Programs -- Chapter 2: Intended and Unintended Consequences: State Policies and Inclusive Access -- Part II: Case Studies -- Chapter 3: Texas A&M University-San Antonio -- Chapter 4: California State University-East Bay -- Chapter 5: Glendale Community College -- Chapter 6: Maricopa Community Colleges -- Chapter 7: Ohio State University -- Chapter 8: Texas State University -- Chapter 9: SUNY Jefferson Community College -- Chapter 10: University of Central Florida.-Chapter 11: University of St. Thomas -- Chapter 12: Norwich University -- Chapter 13: Mid State Technical College -- Chapter 14: Missouri Baptist University -- Chapter 15: Future Directions in Inclusive Access Programs -- Part III: Evidence of Success -- Chapter 16: Adapting Inclusive Access Programs to Ensure the Success of Students with Disabilities -- Chapter 17: The Effects of an Inclusive Access Program on the Cost of Education and Student Debt -- Chapter 18: The Role of Inclusive Access Programs in Student Success: The Effect on Student Grades -- Chapter 19: Improving Student Engagement with Course Content -- Chapter 20: Do Inclusive Access Programs Improve Access to Higher Education? -- Chapter 21: Special Considerations for Inclusive Access Programs and Veteran Students -- Chapter 22: Inclusive Access Programs and Social Learning -- Chapter 23: The Benefits of Instructor Engagement in Inclusive Access programs -- Chapter 24: How Inclusive Access Programs help Texas Colleges meet the TX60x30 Strategic Goals: Empirical Evidence -- Chapter 25: Student Satisfaction with Inclusive Access Programs -- Chapter 26: Costs and Benefits of an Inclusive Access Program at a Public University -- Chapter 27: The Effect of Student Engagement with Course Content on Student Success -- Chapter 28: Student Demographics and Characteristics for Early E-book Adoption -- Chapter 29: Inclusive Access programs and First Generation College student success -- Chapter 30: How do Students access Course Content on campuses with Inclusive Access Programs -- Chapter 31: The Importance and Role of a Faculty Champion in Initiating an Inclusive Access Program -- Chapter 32: Lessons Learned and Future Directions for Inclusive Access Programs.
Keywords: Higher education; Educational technology; Educational policy; Education and state; School management and organization; School administration; Higher Education; Educational Technology; Educational Policy and Politics; Administration, Organization and Leadership